Catalytic performance of nano-sized cobalt copper ferrite on thermal decomposition of ammonium nitrate - Pragnesh N Dave; Ruksana Sirach (Chemical Physics Impact, 2023)
Ammonium nitrate (AN) is being explored as a high energetic oxidizer in propellants. The utilization of pure AN in propellants suffers from a low burning rate. To improve the burning rate, it is important to improve the thermal decomposition characteristics of AN to fasten its thermal decomposition. The effect of CoCuFe2O4 additive was explored to improve the thermos-kinetic parameters of AN's thermal decomposition. Coprecipitation was used to synthesize nanocrystalline CoCuFe2O4. The thermodynamic and kinetic parameters of decomposition of AN: CoCuFe2O4 were investigated using TG-DSC-DTA analysis at 5, 10, and 15 °C min−1. The thermodynamic and kinetic studies suggest that the thermal decomposition of AN+CoCuFe2O4 was more favorable than AN. The decomposition of AN+CoCuFe2O4 occurs at a lower 10 °C lower temperature with ∼44 % decrement in the activation energy and decreased pre-exponential factor. The faster decomposition at a lower temperature was obtained for AN+CoCuFe2O4 composition. Nano-sized particles with efficient optical and polarizable properties made this ferrite material easily separable and eco-friendly for the preparation of a chemical propulsion system based on AN. The AN+CoCuFe2O4 propulsion mixture can be utilized in place of pure AN for better thermal performance in a propellant system. • CoCuFe2O4 was able to influence the thermal decomposition parameters of ammonium nitrate (AN). • AN+CoCuFe2O4 decomposes at lower activation energy with a faster decomposition than pure AN. • Thermodynamics suggest favorable decomposition of AN+CoCuFe2O4 than pure AN.